2018
DOI: 10.1177/0002764218800139
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Aesthetic Cosmopolitanism: Evidence From the Early Consecration of Anglo-American Pop-Rock in Italy

Abstract: This article explores how foreign, recently imported cultural forms can redefine dynamics of legitimation in national cultural fields. Drawing on archival research, the article discusses the early consecration of Anglo-American pop-rock in 1970s Italy and analyzes the articles published by three specialist music magazines. Findings reveal the emergence of a shared pop-rock canon among Italian critics, but also that this "cosmopolitan capital" was mobilized to implement competing editorial projects. Italian cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The second logic can be understood in a musical market in which, both local-national and international genres, composers, groups and singers, operate successfully. We observed that the cultivated syncretics are more pro local-national genres, while both cultivated classicals (with jazz, blues, world music) and cultivated moderns (with foreign pop/rock, rap, reggae or hip-hop) are more inclined towards the prestige of international productions (Bellavance, 2008;Holt, 1997;Varriale, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…The second logic can be understood in a musical market in which, both local-national and international genres, composers, groups and singers, operate successfully. We observed that the cultivated syncretics are more pro local-national genres, while both cultivated classicals (with jazz, blues, world music) and cultivated moderns (with foreign pop/rock, rap, reggae or hip-hop) are more inclined towards the prestige of international productions (Bellavance, 2008;Holt, 1997;Varriale, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, both high status and low status are signalled by non-local tastes. This reminds us that cosmopolitan distinctions are shaped by transnational fields (Varriale, 2021). The 'chain of disdain' reflects the hierarchies and logics of two transnational fields: a global cultural field with English-speaking centres (Kuipers, 2011) and a regional East Asian cultural field with Korean cultural industries at its apex.…”
Section: Discussion and Conclusion: Cultural Cosmopolitan And Chinese...mentioning
confidence: 94%
“…Highbrow cosmopolitan taste is associated with indicators of culturally and economically privileged parental backgrounds and thus works as ‘enhanced’ cultural capital (cf. Varriale, 2021). In addition, what makes Chinese cosmopolitanism uniquely Chinese are its Others: popular Chinese TV, and Hong Kong and South Korean TV.…”
Section: Discussion and Conclusion: Cultural Cosmopolitan And Chinese...mentioning
confidence: 99%